2021
DOI: 10.18488/journal.73.2021.92.209.219
|View full text |Cite
|
Sign up to set email alerts
|

The Enlivenment of Public Opinion in the New Era: Exploring the Power of Social Media on Political Consciousness in Saudi Arabia

Abstract: This research aimed to study how social media has changed the culture of communication in Saudi Arabia. The research surveyed 400 Saudis who use social media in order to discover likely relationships between degree of expression, political consciousness, amount of social media use, apparent attitude climate, government censorship and purposes for using social media. A survey questionnaire was used to answer projected hypotheses and research questions, and the data was analyzed using SPSS software. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This is likely to be attributed to the communication mechanism in Saudi Arabia. For instance, the Saudi government has imposed regulations on speech and expression over the dissemination of material that violates Islamic law, weakens national security, and advances the interests of foreigners [ 66 , 67 ]; and there are government attempts to monitor information on the internet [ 67 ]. This reasoning corresponds with the findings of previous research that power asymmetries in government-public relationships constrain the engagement of local communities (residents and citizens) in the communication practice of place branding; and stakeholder engagement driven by the government could serve as a strategic approach embedded in place branding exercises to enhance internal governance.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be attributed to the communication mechanism in Saudi Arabia. For instance, the Saudi government has imposed regulations on speech and expression over the dissemination of material that violates Islamic law, weakens national security, and advances the interests of foreigners [ 66 , 67 ]; and there are government attempts to monitor information on the internet [ 67 ]. This reasoning corresponds with the findings of previous research that power asymmetries in government-public relationships constrain the engagement of local communities (residents and citizens) in the communication practice of place branding; and stakeholder engagement driven by the government could serve as a strategic approach embedded in place branding exercises to enhance internal governance.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of how to maintain, restore, and promote health will go a long way. The scavengers’ low educational level, on the other hand, limits the contemporary usage of powerful social media platforms for awareness campaigns [ 45 ]. Therefore, the appropriate strategies may include the dissemination of care-seeking and prevention information at dumpsites through loudspeakers, participation of local religious leaders, influential Afghan refugees and scavengers, as well as experts in health promotion programs, employment of mobile network announcement at the scavenging communities and provision of free mobile medical services, particularly at the landfill sites.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that government, nongovernment, profit, and non-profit organizations use communication strategies for public relations through their communication with stakeholders to convince them, change their behaviors and opinions and raise their awareness (Aldekhyyel et al, 2022). However, they did not investigate communication strategies for public relations used on social media during a time of crisis, which will be presented in the following paragraphs (Alsubaie et al, 2021).…”
Section: Communication Strategies By Governments On Social Media and ...mentioning
confidence: 97%
“…Accordingly, the Saudi government started creating content that meets Saudis` desire to know about political and social issues that touch their interests (Gharawi & Alneami, 2020). According to Alsubaie (2021), Saudi officials started their accounts on Twitter after the Arab Spring in 2010/2011 to monitor citizens' opinions (Alsubaie et al, 2021). One such was Abdul-Aziz Khoja, the former Saudi Information Minister who used his social media presence to avoid political revolution (Alrefaee, 2023).…”
Section: Introductionmentioning
confidence: 99%